1981
DOI: 10.1007/bf00618776
|View full text |Cite
|
Sign up to set email alerts
|

Influence of two non-steroidal anti-inflammatory drugs on lipolysis and on plasma post-heparin lipoprotein lipase activity in normal man

Abstract: Indomethacin 50 mg i.v. or p.o. and diclofenac sodium 50 mg p.o. produced a prompt and significant increase in plasma free fatty acid concentration. In 10 subjects who took indomethacin 150 mg/d p.o. for 3 days, plasma post-heparin lipoprotein lipase activity was also significantly increased. The same effect occurred in 9 subjects treated for 3 days with diclofenac sodium 50 mg t.d.s. Since both indomethacin and diclofenac sodium are potent inhibitors of prostaglandin synthetase, these findings are consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…On the other hand, salicylate, indomethacin, or diclofenac increased the net plasma fatty acid concentration in humans [8,25]. The basis for FB s effects on unesterified plasma fatty acid concentrations is unknown.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, salicylate, indomethacin, or diclofenac increased the net plasma fatty acid concentration in humans [8,25]. The basis for FB s effects on unesterified plasma fatty acid concentrations is unknown.…”
Section: Discussionmentioning
confidence: 94%
“…9 It is also lipolytic, as it modulates the production of prostaglandins, which regulate lipolysis; resulting in an increase in total cholesterol, triglycerides as well as free fatty acids. 10 Ajwa fruit was reported to possess protective properties in different pathological conditions, depending on its content of antioxidants (phenols, flavonoids, melatonin, carotenoids, and vitamins A, E, and C) and free radical-scavenging enzymes. 2 Several researchers reported positive effects of Ajwa date flesh extracts on nephrotoxicity as it normalized renal parameters and ameliorated the deterioration of the proximal tubular regions; which agrees with our findings that showed improvemet in the endogenous antioxidant capacity and preserved renal tissue against the detrimental effects of DFS.…”
Section: Discussionmentioning
confidence: 99%
“…9 It is also lipolytic, as it modulates the production of prostaglandins, which regulate lipolysis; resulting in an increase in total cholesterol, triglycerides as well as free fatty acids. 10…”
Section: Discussionmentioning
confidence: 99%
“…54 These abnormalities might be the consequence of 'the significant inhibitory action of DIC on prostaglandin production. 55,56…”
Section: Discussionmentioning
confidence: 99%
“…54 These abnormalities might be the consequence of 'the significant inhibitory action of DIC on prostaglandin production. 55,56 It was found that diclofenac treatment significantly increased the serum MDA level while decreasing serum CAT and GPx activities. These findings were consistent with other reports, 36,57,58 which concluded that DIC treatment increased the amount of the lipid peroxidation marker-MDA, inhibited the antioxidant defense system, and decreased the body's defense mechanism for scavenging free radicals.…”
Section: Biomaterials Science Papermentioning
confidence: 99%